Aplikasi Edpuzzle dalam Penguasaan Kosakata Bahasa Jerman - Rosdiana H; Misnah Mannahali; Abdul Kasim Achmad (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This research aims to determine the planning, implementation and results of improving German vocabulary through Edpuzzle application. This research is a classroom action research consisting of two cycles with each cycle consisting of planning, implementation, observation and reflection stages. This research data consists of two types of data, namely qualitative data which is a description of the results of implementation and observation during learning and quantitative data in the form of student vocabulary mastery test results. The average value of vocabulary improvement of X MIPA 7 students in cycle I was 68.84% then in cycle II it increased to 86.08%. The results showed that the use of Edpuzzle application can improve students' mastery of German vocabulary during learning.Keywords: Vocabulary, Media, German